A Pedagogical Note on the Long Run of Macro Economic Models - Peter McAdam (University of Kent, Department of Economics, 1998)
This paper surveys and motivates the reasons for incorporating explicit long run of supply features into applied estimated macro economic models. It defines some basic stability conditions for such models and illustrates elements of long run considerations with reference to a small (22 equation) prototype model which fashions itself after many current models. It also shows that many of the key decisions when setting up the long run extended simulation horizon reduce to a relatively small number of relationships.
Keywords: C51; C52; 330; Long run; stability; macro models; closures.; Ökonometrisches Makromodell; Theorie